Comparison of Conventional Surgical Turbinoplasty Versus Microdebrider Assisted Turbinoplasty in Cases of Inferior Turbinate Hypertrophy - Salman Ali, Haitham Akaash, Arslan Akhtar, Asmara Hussain, Lt Col Ghulam Fareed, Sana Muhammed Sadiq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the conventional surgical turbinoplasty versus microdebrider assisted turbinoplasty in cases of inferior turbinate hypertrophy. Design of the Study: It was a cross-sectional survey. Place and Duration of Study: This study was carried at the Department of ENT Nishtar Medical University and Hospital, Multan from January 2022 to June 2022. Patients and Methods: Patients with hypertrophy of the inferior turbinates, the most common cause of nasal obstruction, were split into two groups of 30. The size of the inferior turbinates was classified as Grade I if they took up less than a third of the nasal cavity, Grade II if they took up more than a third but less than half, and Grade III if they took up more than half. Each group had either a standard partial inferior turbinectomy or a turbinoplasty with the help of a microdebrider. Visual evaluation was used to categorise blood loss during and after surgery. Patients were checked on at 1, 2, 4, and 6 months after surgery. Relief from symptoms and the occurrence of problems such crusting and synechiae formation were evaluated. Results of the Study: Both groups showed comparable significant improvements in nasal blockage. Most patients in the CPIT group experienced intraoperative blood loss of grade II (66.66%) or grade III (10%). When the packs were taken off, 60% of patients experienced grade I blood loss, 36.66% experienced grade II blood loss, and 3% experienced grade III blood loss after surgery. Most patients (46%) and surgeons (40%) in the MAT group experienced grade II or higher intraoperative blood loss. The majority of patients' postoperative blood loss was classified as grade I. Six months later, 6.66 percent of the CPIT group had acquired crusting, and 6.66 percent had developed synechiae. Those that received MAT did not have these problems. Practical implication: The choice of surgical procedure is up to the surgeon's attitude and experience due to the lack of agreement regarding their efficacy. That’s why we compared the effectiveness of these treatment methods for turbinate reduction in order to provide evidence to evaluate the results of the several surgical techniques in local population. Conclusion: According to the findings, both surgical approaches are effective in addressing nasal blockage. Complications are less likely to occur with microdebrider-assisted inferior turbinoplasty since the mucosa and nasal physiology are preserved. Keywords: Microdebrider assisted inferior turbinoplasty, Hypertrophied inferior turbinate, Conventional partial inferior turbinectomy,